Active back thrust in the eastern Taiwan suture revealed by the 2013 Rueisuei earthquake: Evidence for a doubly vergent orogenic wedge?. Issue 10 (28th May 2014) - Chuang, Ray Y.; Johnson, Kaj M.; Kuo, Yu‐Ting; Wu, Yih‐Min; Chang, Chien‐Hsin; Kuo, Long‐Chen
Abstract Rapid exhumation of 3–10 mm/yr of the Taiwan metamorphic range is often explained as the unroofing of the retrowedge of a doubly vergent mountain belt. Yet, to date, the Central Range fault forming the boundary of the retrowedge has displayed no definitive evidence for recent seismic activity and no unambiguous geomorphic expression over much of the fault. The 2013 M6.4 Rueisuei reverse‐faulting earthquake nucleated at the eastern boundary of the retrowedge and appears to illuminate the west dipping Central Range fault. We estimate the fault geometry and coseismic slip distribution using a uniform stress drop slip inversion and surface displacements derived from GPS and strong‐motion data. We identify a 42° dipping blind reverse fault, consistent with the previously proposed buried Central Range fault beneath the highly active Longitudinal Valley fault. This earthquake may be the first indication that rapid exhumation and uplift occur along a distinct fault structure bounding the eastern margin of the Taiwan retrowedge.